2017
DOI: 10.1007/s00520-017-3777-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breast cancer treatments on sleep quality 1 year after cancer diagnosis

Abstract: Purpose The increasing number of women living longer with potential side effects of breast cancer treatment highlights the need of a comprehensive assessment of its burden. Therefore, we aimed to quantify the relation between different breast cancer treatments and sleep quality 1 year after diagnosis. Methods A cohort of 502 newly diagnosed breast cancer patients was prospectively followed. Sleep quality was evaluated with the Pittsburgh Sleep Quality Index (PSQI), at baseline and at the 1-year follow-up. Odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
0
19
1
3
Order By: Relevance
“…Although the current study did not identify any association between education and sleep disturbance in patients with NPC before treatment, a previous study reported that education was positively associated with an improvement in sleep quality among patients with poor sleep before breast cancer treatments 38 . Furthermore, less education was a significant predictor for poorer overall sleep in oncology patients at the initiation of chemotherapy 39 .…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Although the current study did not identify any association between education and sleep disturbance in patients with NPC before treatment, a previous study reported that education was positively associated with an improvement in sleep quality among patients with poor sleep before breast cancer treatments 38 . Furthermore, less education was a significant predictor for poorer overall sleep in oncology patients at the initiation of chemotherapy 39 .…”
Section: Discussioncontrasting
confidence: 92%
“…Finally, in this study, factors that predicted poor sleep quality of patients with NPC prior to the initiation of treatment only included demographic and personal characteristics and cancer-specific variables. However, a great number of previous studies have shown that pain, depression, anxiety, fatigue, and cognitive function were all associated with sleep quality in cancer patients 38 , 40 , 41 . Furthermore, these symptoms seldom occur in isolation.…”
Section: Discussionmentioning
confidence: 96%
“…Women who report poor sleep quality prior to chemotherapy often remain poor sleepers afterwards, and a percentage of good sleepers become poor sleepers, with 30-60% of patients affected [4]. Different BC treatments increase the risk of impaired sleep quality, thus contributing to the global disability associated with cancer treatments [5]. When poor sleep occurs with depression in patients with cancer, epidemiological observations link these symptoms to cancer morbidity and mortality risk [6].…”
Section: Introductionmentioning
confidence: 99%
“…When poor sleep occurs with depression in patients with cancer, epidemiological observations link these symptoms to cancer morbidity and mortality risk [6]. In addition, until there is routine screening, assessment, and treatment of sleep deficiency, an increasing number of BC survivors are likely to experience lower quality of life (QOL) [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…About 75% of Americans report experiencing some type of sleep disturbance (Stanford Center for Sleep Sciences and Medicine, 2017), and 60% of older women diagnosed with breast cancer report poor sleep quality (Costa et al, 2014). Many individuals complain of problems sleeping even before receiving any cancer treatment (Fontes, Pereira, Costa, Gonçalves, & Lunet, 2017). Treatment for breast cancer often increases problems associated with poor sleep during and after cancer therapy (Costa et al, 2014).…”
mentioning
confidence: 99%